Unchained memories [videorecording (DVD)] : readings from the slave narratives - Lennon, Thomas, 1970-; Bell, Ed; Bassett, Angela; Boatman, Michael, 1964-; Browne, Roscoe Lee; Cheadle, Don; Davis, Ossie; Dee, Ruby; Guillaume, Robert; Guy, Jasmine; Jackson, Samuel L.; Pounder, C. C. H.; et al. (HBO Documentary Films : Distributed by HBO Video, 2003)
When the Civil War ended in 1865, more than 4 million slaves were set free. By the late 1930's, 100,000 former slaves were still alive. In the midst of the Great Depression, journalists and writers traveled the country to record the memories of the last generation of African-Americans born into bondage. Over 2,000 interviews were transcribed as spoken, in the vernacular of the time, to form a unique historical record.